2012
DOI: 10.1007/s00429-012-0444-z
|View full text |Cite
|
Sign up to set email alerts
|

Brain structures associated with executive functions during everyday events in a non-clinical sample

Abstract: Executive functions involve control processes such as goal-oriented planning, flexible strategy generation, sustaining set maintenance, self-monitoring, and inhibition. Executive functions during everyday events (EFEEs) are distinct from those measured under laboratory settings; the former can be severely impaired while the latter remain intact. Non-routine everyday problems due to executive dysfunctions affect individual functioning in everyday life and are of great clinical interest. Despite the importance o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
45
1
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 84 publications
(57 citation statements)
references
References 129 publications
(172 reference statements)
6
45
1
1
Order By: Relevance
“…Thus there were 27 studies on prefrontal volume and 7 studies on cortical thickness. Six papers (Burzynska et al, 2012; Gautam et al, 2011; Gianaros et al, 2006; Gur et al, 2000; Kochunov et al, 2009; Takeuchi et al, 2013) examined two separate samples of different age or gender treated as independent sources of the effect size. Final analyses were conducted on 31 independent samples on prefrontal volume, and 10 independent samples on prefrontal gray matter thickness.…”
Section: Methodsmentioning
confidence: 99%
“…Thus there were 27 studies on prefrontal volume and 7 studies on cortical thickness. Six papers (Burzynska et al, 2012; Gautam et al, 2011; Gianaros et al, 2006; Gur et al, 2000; Kochunov et al, 2009; Takeuchi et al, 2013) examined two separate samples of different age or gender treated as independent sources of the effect size. Final analyses were conducted on 31 independent samples on prefrontal volume, and 10 independent samples on prefrontal gray matter thickness.…”
Section: Methodsmentioning
confidence: 99%
“…Searching for structural brain-behavior correlation with this approach is often performed by introducing several regressors (or predictors) in addition to the behavioral measure of interest (X) in the design matrix, such as age, gender, TBV, and a behavioral measure of general cognitive functioning (e.g. (Takeuchi et al 2010(Takeuchi et al , 2013Genon et al 2014)). …”
Section: Limitations Of the Voi Approachmentioning
confidence: 99%
“…There is little consensus with regard to the specific regions of PFC associated with individual differences in discrete EFs and, even more basically, with regard to the direction of the relationship between neuroanatomical variables and performance on EF tasks (i.e., in some cases increases in GM morphometry or FA is predictive of better EF performance and in other cases the relationship is reversed). For example, some results regarding GM volume/density in relation to EF in healthy adults (often healthy control samples) have shown that increased GM volume/density is associated with better EF performance (Elderkin-Thompson et al 2008, 2009; Ettinger et al 2005; Gunning-Dixon and Raz 2003; Head et al 2009; Kaller et al 2012; Nakamura et al 2008; Newman et al 2007; Ruscheweyh et al 2012; Zimmerman et al 2006), while others show that decreased GM volume/density is associated with better EF performance (Duarte et al 2006; Elderkin-Thompson et al 2008, 2009; Gautam et al 2011; Kaller et al 2012; Koutsouleris et al 2010; Raz et al 1998; Salat et al 2002; Takeuchi et al 2012a, b). Though very few exist, studies examining the relationships of neuroanatomical features other than volume/density with EF in healthy adults similarly do not implicate common, overlapping regions across studies, but do converge on the general direction of neuroanatomy/EF relationships.…”
Section: Introductionmentioning
confidence: 99%